2013
DOI: 10.1109/tcomm.2013.072913.120344
|View full text |Cite
|
Sign up to set email alerts
|

Optimum and Sub-Optimum Receivers for OFDM Signals with Strong Nonlinear Distortion Effects

Abstract: Abstract:In this paper we consider the optimum detection of OFDM (Orthogonal Frequency Division Multiplexing) signals with strong nonlinear distortion effects. It is shown that the optimum performance with strong nonlinear distortion effects is not as bad as one might expect and can even be better than the performance with conventional, linear transmitters. To achieve these excellent performances we should employ receivers able to take advantage of the information associated to transmitted data symbols that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…Recently, another point of view was given to the nonlinear distortion. In [18][19][20] it was demonstrated that the nonlinear distortion has information on the transmitted signals and, instead of being regarded as noise, it can be considered to be useful information that can be harvested by optimum receivers. The optimum detection can provide two types of gain: an energy gain and a diversity gain that can be explored in frequency-selective channels.…”
Section: Optimum Performance Of Ce-ofdm Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, another point of view was given to the nonlinear distortion. In [18][19][20] it was demonstrated that the nonlinear distortion has information on the transmitted signals and, instead of being regarded as noise, it can be considered to be useful information that can be harvested by optimum receivers. The optimum detection can provide two types of gain: an energy gain and a diversity gain that can be explored in frequency-selective channels.…”
Section: Optimum Performance Of Ce-ofdm Signalsmentioning
confidence: 99%
“…In order to do that, we focus our attention in the computation of an approximation of the pairwise error probability (PEP), that is related to the squared Euclidean distance between two CE-OFDM signals and can provide an insight to the optimum performance. In this section, we study the squared Euclidean distance between two CE-OFDM signals in both AWGN and frequency-selective channels, and present the correspondent asymptotic BER making use of the results of [19,20].…”
Section: Optimum Performance Of Ce-ofdm Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is better than the SR. However, keeping in mind the fact that the distortions contain information about the transmitted signal, the best approach is to use the whole received signal, including distortions, in the receiver [7].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is also known as the Maximum Likelihood (ML) receiver. A suboptimal solution to the above problem is given in [7]. In this paper we propose a suboptimal solution based on the idea of a class of global minima solutions coupled with a gradient minima search.…”
Section: Introductionmentioning
confidence: 99%